2006
DOI: 10.1093/aje/kwj104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Infant Birth Characteristics and Hepatoblastoma

Abstract: Hepatoblastoma is a rare embryonal tumor with unknown etiology. The authors conducted a case-cohort study using public health surveillance data sets to examine perinatal risk factors for hepatoblastoma. Hepatoblastoma cases (n = 58) diagnosed between 1985 and 2001 were identified from the New York State Cancer Registry and were matched to electronic birth records for 1985-2001 from New York State, excluding New York City. Controls (n = 6,056) were selected from the birth cohorts for the same years. Having a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
115
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 52 publications
6
115
3
5
Order By: Relevance
“…Very low birth weight has emerged over the past 15 years as a potent risk factor for hepatoblastoma (Feusner et al, 1998;Tanimura et al, 1998;Reynolds et al, 2004;Ansell et al, 2005;McLaughlin et al, 2006). We have now confirmed this association in the paediatric population of Minnesota.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Very low birth weight has emerged over the past 15 years as a potent risk factor for hepatoblastoma (Feusner et al, 1998;Tanimura et al, 1998;Reynolds et al, 2004;Ansell et al, 2005;McLaughlin et al, 2006). We have now confirmed this association in the paediatric population of Minnesota.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings were not noted in studies in California (Reynolds et al, 2004) and New York (McLaughlin et al, 2006), and there was not an elevated rate in Ho Chi Minh City, Vietnam (Nguyen et al, 2000). Our observation was therefore novel and independent of birth weight.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…13 Nevertheless, few studies have reported the incidence of cancer in the already large and growing population of children born after fertility treatment and the results are inconsistent. While some studies showed increased risks for all cancers 14 and for specific types of cancer, such as retinoblastoma, 15 neuroblastoma, 6 leukemia, [16][17][18] and hepatoblastoma, 19,20 others found no association. [21][22][23][24][25][26][27][28][29][30][31][32] However, the main part of these studies are characterized by small sample sizes, short follow-up periods and lack of information on the use of fertility drugs.…”
mentioning
confidence: 98%